2019
DOI: 10.1111/are.13953
|View full text |Cite
|
Sign up to set email alerts
|

Effects of replacing fish meal with mussel (Cristaria plicata) meat on growth, digestive ability, antioxidant capacity and hepatic IGF-I gene expression in juvenile Ussuri catfish (Pseudobagrus ussuriensis)

Abstract: An 8-week feeding trial was implemented to evaluate the effects of replacing fish meal (FM) with mussel (Cristaria plicata) meat (MM) on growth, digestive ability, antioxidant capacity and hepatic insulin-like growth factor I (IGF-I) gene expression of juvenile Ussuri catfish (Pseudobagrus ussuriensis). Three isonitrogenous and isolipidic diets were formulated to include 0, 177.5 and 355.1 g/kg of MM, accordingly, replacing 0% (M 0 , control), 50% (M 1 ) and 100% (M 2 ) of FM protein, respectively. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…qRT-PCR reaction was programmed as follows: 94°C for 30 s, and followed by 40 cycles for 5 s at 94°C, 30 s at 60°C and 10 s at 72°C. Relative expression levels of all genes were determined using the 2 −ΔΔCT method ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…qRT-PCR reaction was programmed as follows: 94°C for 30 s, and followed by 40 cycles for 5 s at 94°C, 30 s at 60°C and 10 s at 72°C. Relative expression levels of all genes were determined using the 2 −ΔΔCT method ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…Expression levels of the target genes were normalized to the housekeeping genes β-actin and GAPDH as endogenous controls. qRT-PCR reaction was programmed as follows: 94 • C for 30 s, and followed by 40 cycles for 5 s at 94 • C, 30 s at 60 • C and 10 s at 72 • C. Relative expression levels of all genes were determined using the 2 − CT method (17).…”
Section: Genes Expression Analysismentioning
confidence: 99%
“…However, this fish is facing the problem of immune suppression and liver damage with the development of intensive farming. To date, some experiments about dietary nutrition requirement of this fish have been conducted and the effect of different vegetable protein (soybean meal, vegetable meal, cotton meal and corn protein) and animal protein (meat and bone meal, mussel meal) replacing fish meal had been studied in our laboratory (Bu et al, 2017;Luo, 2019;Wang et al, 2020). Moreover, a preliminary study about the health function of YC on Pseudobagrus ussuriensis has been explored (Bu et al, 2019).…”
Section: Pseudobagrus Ussuriensis Is An Important Indigenous Species Inmentioning
confidence: 99%
“…However, due to the large-scale and intensive fish farming, the shortage of fishmeal is prominent. To date, several studies have reported feasibility in replacing fishmeal with different proteins, including corn gluten meal [15], rapeseed meal [16], cottonseed meal [17], meatand bone meal [18] as well as mussel (Cristaria plicata) meat meal [19] in P. ussuriensis. But there is limited message regarding the potential role of dietary YC as partial FM substitute on growth performance and healthy status for P. ussuriensis.…”
Section: Introductionmentioning
confidence: 99%